Hoạt động magma nội mảng lãnh thổ Việt Nam và khoáng sản liên quan - Trần, Trọng Hoá (2011)
Tác giả: Trần Trọng Hoá, TS; Ngô Thị Phượng, TS; Trần Tuấn Anh, TS; Bùi Ân Niên, TS -- Từ khóa: Magma; Khoáng sản; Việt Nam